A Comprehensive Computational Fluid Dynamics (CFD) Analysis of the Effect of Blade Number on the Performance and Rotational Characteristics of Hydrokinetic Turbines - Rachman , Aditya; Samhuddin; Kadir, Abdul; Ramadhan, Anwar Ilmar; Firmansyah (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2026)
The number of blades in hydrokinetic power systems is a fundamental aspect of their design. This number affects not only the investment and mechanical loads but also the performance and rotational characteristics. The relationship between the number, performance, and rotational aspects is complex, however there are currently insufficient explanations for this connection. This study examines the complex interaction between them using a steady Computational Fluid Dynamics (CFD) method based on Reynolds-Averaged Navier-Stokes (RANS) simulation. The results suggest that turbines with a higher number of blades are more effective than those with a smaller number in regions where the Tip Speed Ratio (TSR) is less than 3. Above this range, turbines with lower blade numbers perform more effectively than ones with higher numbers. The study indicates that increasing the surface area of the turbine blades can efficiently boost the torque generated at low TSR levels, leading to high-performance turbines with a higher blade number. However, when the turbine's TSR is high, an intricate flow phenomenon takes place. This phenomenon is caused by the excessive number of blades, which generates a blockage effect that changes the direction and strength of the flow over the blade. As a result, the lift decreases. This work provides novel insights into the mechanism that governs the performance and rotational properties of turbines with varying numbers of blades. Engineers can derive advantages from comprehending the effect of blade number when choosing the generator and the transmission of hydrokinetic power systems.